Pengembangan LKS Dengan Model IDL Untuk Melatihkan Keterampilan Proses Sains Pada Pokok Bahasan Listrik Dinamis Di SMAN 5 Banjarmasin - Sasanti, Merry; Hartini, Sri; Mahardika, Andi Ichsan (Berkala Ilmiah Pendidikan Fisika, 2017)
Learning physics is one of the problems frequently encountered in learning activities in school, especially at the high school level. The students are not trained to develop the skills process of science in solving a problem or symptom of physics. In addition, LKS often met at school only a summary of the subject matter, and it is exercise which consists of questions. LKS of this type does not train students to do the investigation process. The study aims to determine the feasibility of LKS with the model IDL to train skills the process of science students, in order to particularly describe (1) validity of LKS are developed, (2) practicalities LKS are developed, and (3) effectiveness of LKS, which was developed. The research method is research and development with model of developmen Dick and Carey. Data obtained through a validation LKS, feasibility RPP, observation skills the process of science and students test score. The results showed that (1) validation LKS which was developed according to validator is very good, (2) practicality of learning which is based on the feasibility RPP is very good, (3) effectiveness of learning based on test (THB) and establishment of skills the process of science students to LKS which was developed quiete good. Conclusion is obtained based on research which is LKS with model IDL to train skills the process of science in the dearth of power dynamic in SMAN 5 Banjarmasin unfit for use